Varieties of Subjectivity. Issue 5 (December 2020) - Godfrey-Smith, Peter
Abstract : In human conscious experience, many features are present in combination: objects are presented through the senses, information from different sensory modalities is integrated, events are marked with value, and we have a sense of our own location and state. Which of these might come before others in plausible evolutionary trajectories, or do they form a tight package of correlated features that cannot readily be dissociated? I take a comparative approach to these questions, focusing on a distinction between sensory and evaluative aspects of experience and looking at the distribution of subjectivity-relevant features in a range of invertebrate animals.